Asymmetric Reduction of Substituted 2‐Tetralones by Thermoanaerobacter pseudoethanolicus Secondary Alcohol Dehydrogenase. Issue 8 (6th April 2017) - Bsharat, Odey; Musa, Musa M.; Vieille, Claire; Oladepo, Sulayman A.; Takahashi, Masateru; Hamdan, Samir M.
Abstract: Ketones bearing two bulky substituents, named bulky–bulky ketones, were successfully reduced to their corresponding optically enriched alcohols by using various mutants of Thermoanaerobacter pseudoethanolicus secondary alcohol dehydrogenase (TeSADH). Substituted 2‐tetralones, in particular, were reduced to 2‐tetralols with high conversion and high enantioselectivity. The pharmacological importance of substituted 2‐tetralols as key drug‐building blocks makes our biocatalytic reduction method a highly essential tool. We showed that changing the position of the substituent on the aromatic ring of 2‐tetralones impacts their binding affinity and the reaction maximum catalytic rate. Docking studies with several TeSADH mutants explain how the position of the substituent on the tetralone influences the binding orientation of substituted 2‐tetralones and their reaction stereoselectivity. Abstract : Perfect fit : Substituted 2‐tetralones are reduced to optically enriched 2‐tetralols by using mutants of Thermoanaerobacter pseudoethanolicus secondary alcohol dehydrogenase. Docking studies explain how the substituent's position on the 2‐tetralone influences the binding orientation of the substrates and their reaction stereoselectivity.